Suicide resilience, identity crisis and quality of life in burned adolescents - Fateme Mohammadi; Khodayar Oshvandi; Seyed Reza Borzou; Masood Khodaveisi; Salman Khazaei; Mohammad Reza Shokouhi; Fatemeh Nouri; Mohammad Taheri; Majid Kalbasi (Wiley, 2023)
Abstract Aim The aim of this study was to investigate the relationship between identity crisis and suicide resilience and quality of life in adolescents with burns in Iranian society. Design A cross‐sectional study. Methods Four hundred thirty adolescents with burn in three hospitals were selected via convenience sampling. They completed questionnaires online. Data were analysed by SPSS software version 22. Results Findings showed a strong and inverse correlation between identity crisis with suicide resilience (r = −.92, p < .001) and quality of life (r = −.87, p < .001). Variables of suicide resilience, being a child of a divorced family, cause of burns, extent of burn, financial situation, gender and age can predict 68.74% of the variance in identity crisis in these patients. Patient or Public Contribution Adolescents with burns suffer from an identity crisis, and although they report high resilience to suicide, they have a mediocre quality of life. Therefore, it is suggested that basic planning and extensive support be taken to improve physical and mental health, promote the quality of life and consequently reduce the identity crisis in these adolescents.